The Effect of Mindfulness and Acceptance Training on Body Image Concerns, Mental Skills and Free Throw Shooting Performance in Male Basketball Players with Wheelchairs - Farshad Abbasi; Rokhsareh Badami; Daruosh Jalali (پژوهشنامه روانشناسی مثبت, 2018)
The present study aimed at investigating the effect of mindfulness and acceptance training on body image concerns, mental skills and free throw shooting performance. The participants included 22 male basketball players with wheelchairs aged between 25 and 45 who were playing in the National Basketball League Second Division. The participants were homogenized by age and level of spinal cord injury and randomly assigned into experimental and control groups. The experimental group received eight sessions (each 90 min.) of mindfulness and acceptance training while the control group were doing their daily activities. The data were collected using OMSAT-3, Body Image Concerns Inventory and AAHPERD Basketball test and were analyzed using MANCOVA. The findings revealed that mindfulness and acceptance training fostered mental skills and free throw shooting performance of the male basketball players. Therefore, participation in mindfulness and acceptance training with the aim of fostering mental skills and basketball performance is recommended.